3, 4-Dihydroquinazoline derivatives inhibit the activities of cholinesterase enzymes. Issue 5 (1st March 2017) - Park, Byeongyeon; Nam, Ji Hye; Kim, Jin Han; Kim, Hyoung Ja; Onnis, Valentina; Balboni, Gianfranco; Lee, Kyung-Tae; Park, Jeong Ho; Catto, Marco; Carotti, Angelo; Lee, Jae Yeol
Graphical abstract: Abstract: A series of 3, 4-dihydroquinazoline derivatives consisting of the selected compounds from our chemical library on the diversity basis and the new synthetic compounds were in vitro tested for their inhibitory activities for both acetylcholinesterase (AChE, from electric eel) and butyrylcholinesterase (BChE, from equine serum) enzymes. It was discovered that most of the compounds displayed weak AChE and strong BuChE inhibitory activities. In particular, compound8b and8d were the most active compounds in the series against BChE with IC50 values of 45 nM and 62 nM, as well as 146- and 161-fold higher affinity to BChE, respectively. To understand the excellent activity of these compounds, molecular docking simulations were performed to get better insights into the mechanism of binding of 3, 4-dihydroquinazoline derivatives. As expected, compound8b and8d bind to both catalytic anionic site (CAS) and peripheral site (PS) of BChE with better interaction energy values than AChE, in agreement with our experimental data. Furthermore, the non-competitive/mixed-type inhibitions of both compounds further confirmed their dual binding nature in kinetic studies.